URGENSI DIGITAL LIBRARY DALAM PEMBERDAYAAN MADRASAH: Penggunaan Maktabah Syamilah versi 2.11 Dalam Peningkatan Kualitas Pembelajaran Guru di MAN 1 Model Bandar Lampung - Ghozali, Abdul Malik (IAIN Ponorogo, 2017)
Madrasah is an Islamic educational institution that has a big role in development in the country. However, there are still some obstacles in his journey, including the lack of knowledge of teachers in the use of technology in learning such as the use of digital libraries. In this paper describes the efforts of MAN 1 Bandar Lampung in empowering the madrasah and the effectiveness of digital libraries in empowering the madrasah. The results of this research are: first, empowerment conducted in MAN 1 Bandar Lampung through several stages, awareness or enlightenment, intensive capacity and empowerment. Secondly, there are some improvement of teachers skill in the use of digital library, such as in searching verses of Koran and His commentary, referring some Hadith of the Prophet and his explanatory, seeking references for strengthening the subjects in the class, discussing problem solving and reviewing Arabic Grammar and Arabic Sciences.Ø§ÙÙ Ø¯Ø±Ø³Ø© ÙÙ Ù Ø¤Ø³Ø³Ø© ØªØ¹ÙÙÙ ÙØ© Ø¥Ø³ÙØ§Ù ÙØ© ÙÙØ§ Ø¯ÙØ± ÙØ¨ÙØ± ÙÙ Ø§ÙØªÙÙ ÙØ© ÙÙ Ø§ÙØ¨ÙØ§Ø¯. ÙÙ Ø¹ Ø°ÙÙØ ÙØ§ ØªØ²Ø§Ù ÙÙØ§Ù Ø¨Ø¹Ø¶ Ø§ÙØ¹ÙØ¨Ø§Øª ÙÙ Ø±ØÙØªÙØ§Ø Ø¨Ù Ø§ ÙÙ Ø°ÙÙ Ø¹Ø¯Ù Ù Ø¹Ø±ÙØ© Ø§ÙÙ Ø¹ÙÙ ÙÙ ÙÙ Ø§Ø³ØªØ®Ø¯Ø§Ù Ø§ÙØªÙÙÙÙÙØ¬ÙØ§ ÙÙ Ø§ÙØªØ¯Ø±ÙØ³ Ù Ø«Ù Ø§Ø³ØªØ®Ø¯Ø§Ù Ø§ÙÙ ÙØªØ¨Ø§Øª Ø§ÙØ±ÙÙ ÙØ©. ÙÙ ÙØ°Ù Ø§ÙÙØ±ÙØ© ØªØµÙ Ø¬ÙÙØ¯ Ø§ÙÙ Ø¯Ø±Ø³Ø© Ø§ÙØ«ÙÙÙØ© Ø§ÙØÙÙÙ ÙØ© Ø§ÙÙÙ ÙØ°Ø¬ÙØ© Ø§ÙØ£ÙÙÙ Ø¨ÙØ¯Ø± ÙØ§Ù Ø¨ÙÙØ¬ ÙÙ ØªÙØ¹ÙÙ Ø§ÙÙÙÙ Ø§ÙÙ Ø¯Ø±Ø³ÙØ© ÙÙØ¹Ø§ÙÙØ© Ø§ÙÙ ÙØªØ¨Ø§Øª Ø§ÙØ±ÙÙ ÙØ© ÙÙ ØªÙØ¹ÙÙ Ø§ÙÙ Ø¯Ø±Ø³Ø©. Â ÙÙØªØ§Ø¦Ø¬ ÙØ°Ø§ Ø§ÙØ¨ØØ« ÙÙ: Ø£ÙÙØ§Ø Ø§ÙØªÙØ¹ÙÙ Ø§ÙØ°Ù Ø£Ø¬Ø±Ù ÙÙ Ø§ÙÙ Ø¯Ø±Ø³Ø© Ø§ÙØ«ÙÙÙØ© Ø§ÙØÙÙÙ ÙØ© Ø§ÙÙÙ ÙØ°Ø¬ÙØ© Ø§ÙØ£ÙÙÙ Ø¨ÙØ¯Ø± ÙØ§Ù Ø¨ÙÙØ¬ Ù Ù Ø®ÙØ§Ù Ø¹Ø¯Ø© Ù Ø±Ø§ØÙØ ÙÙÙ Ø§ÙØªÙØ¹ÙØ© Ø£Ù Ø§ÙØªÙÙÙØ±Ø ÙØªÙØ«ÙÙ Ø§ÙÙØ¯Ø±Ø§Øª ÙØ§ÙØªÙØ¹ÙÙ. ÙØ«Ø§ÙÙØ§Ø ÙÙØ§Ù Ø¨Ø¹Ø¶ Ø§ÙØªØ±ÙÙØ§Øª ÙÙØ¯Ø±Ø© Ø§ÙÙ Ø¹ÙÙ ÙÙ ÙÙ Ø§Ø³ØªØ®Ø¯Ø§Ù Ø§ÙÙ ÙØªØ¨Ø© Ø§ÙØ±ÙÙ ÙØ©Ø ÙÙ Ø§ ÙÙ Ø§ÙØØ§Ù ÙÙ Ø§ÙØ¨ØØ« Ø¹Ù Ø¢ÙØ§Øª Ù Ù Ø§ÙÙØ±Ø¢Ù Ø§ÙÙØ±ÙÙ ÙØªÙØ³ÙØ±ÙØ§Ø ÙØªØ®Ø±ÙØ¬ Ø§ÙØ£ØØ§Ø¯ÙØ« Ø§ÙÙØ¨ÙÙØ© ÙØ´Ø±ØÙØ§Ø ÙØ§ÙØØµÙÙ Ø¹ÙÙ Ù Ø¬Ù ÙØ¹Ø© Ø§ÙÙ Ø±Ø§Ø¬Ø¹ ÙØªØ¹Ø²ÙØ² Ø§ÙÙ ÙØ§Ø¯ Ø§ÙØ¯Ø±Ø§Ø³ÙØ© Ø§ÙÙ Ø¯Ø±ÙØ³Ø© ÙÙ Ø§ÙØµÙØ ÙÙ ÙØ§ÙØ´Ø© Ø¨ØØ« Ø§ÙÙ Ø³Ø§Ø¦Ù ÙØ¯Ø±Ø§Ø³Ø© Ø§ÙÙØÙ ÙØ§ÙØµØ±Ù ÙØ§ÙØ¹ÙÙÙ Ø§ÙØ¹Ø±Ø¨ÙØ©.